Breakthrough - Dawson, Roxann; Nieporte, Grant; Franklin, DeVon; Metz, Chrissy, 1980-; Grace, Topher, 1978-; Lucas, Josh; Ruiz, Marcel, 2003-; Haysbert, Dennis; Staab, Rebecca; Trammell, Sam, 1971-; Colter, Mike, 1976-; Zarvos, Marcelo; et al. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2019)
Based on the inspirational true story of one mother's unfaltering love in the face of impossible odds. When Joyce Smith's adopted son John falls through an icy Missouri lake, all hope seems lost. But as John lies lifeless, Joyce refuses to give up. Her steadfast belief inspires those around her to continue to pray for John's recovery, even in the face of every case history and scientific prediction. A reminder that faith and love can create a mountain of hope, and sometimes even a miracle.
DVD, NTSC region 1, anamorphic widescreen (2.39:1) presentation; Dolby Digital 5.1, Dolby Digital 2.0.
In English, Spanish, or French; Spanish or French subtitles; English subtitles for the deaf and hard-of-hearing (SDH); closed-captioned; English descriptive audio track for people with visual disabilities.
Title from disc surface.
Chrissy Metz, Topher Grace, Josh Lucas, Marcel Ruiz, Dennis Haysbert, Rebecca Staab, Sam Trammell, Mike Colter.
Music, Marcelo Zarvos ; film editor, Maysie Hoy ; production designer, Gae Buckley ; director of photograhpy, Zoran Popovic.
Originally released as a motion picture in 2019.
Keywords: Smith, Joyce -- (Author at FaithWords (Firm)) -- Drama; Faith -- Drama; Accidents -- Drama; Mothers and sons -- Drama; Near-death experiences -- Drama; Missouri -- Social life and customs -- 21st century -- Drama; Film adaptations; Religious films; Feature films; Fiction films; Melodramas (Motion pictures); Video recordings for the hearing impaired; Video recordings for people with visual disabilities